Partners shape partnerships - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
If the enlarged village which is Wageningen, and home to CTA s headquarters, has no baobab tree for sheltering discussions, it is only for reasons of climate. For, indoors, those intense, familiar, time-consuming, fruitful discussions indeed take...